La teoría del juego del ajedrez de Alf Ross y su aplicación en el orden jurídico peruano - Franciskovic Ingunza, Millitza (2022)
A comparative analytical study on the validity of the law is offered by the Danish legal philosopher Alf Ross, in his work: "On Law and Justice". Ross will begin his academic journey through a careful observation of the game of chess and argues that the concept of the "validity of law" must be analyzed and interpreted in the same way as the concept of the "current rule of chess". And it is here, where he will provide the meaning of current law. It will also clarify the content of the legal order with the explanation regarding to whom it is directed and what is the meaning of the rules of a national legal order, differentiating and defining for this purpose the rules of conduct and the rules of competence in order to elucidate and understand with the parameters of Ross' thought, the current law and its application in the Peruvian legal order.